Antioxidant Activity from Glucomannan Degradation Product Using β- mannanase Enzyme with DPPH Method (Universitas Muhammadiyah Yogyakarta, 2025)
Antioxidants are defined as chemical components or compounds that can inhibit damage due to the oxidation process. Glucomannan, which is formed from a polysaccharide called mannan, has various benefits, such as anti-inflammatory, hypoglycemic, hypolipidemic, and antioxidant properties. This research aims to determine the antioxidant activity of glucomannan degradation using the β-Mannanase enzyme and the effect of temperature and pH on its antioxidant activity. Researchers carried out three degradation variations in the form of pH variations (5.5, 7, and 9) and temperature variations (45℃, 55℃, and 65℃), which resulted in 9 samples. The method used for antioxidant testing is DPPH. The antioxidant activity parameters were assessed based on the IC50 value obtained from the antioxidant test results. The best degradation results of glucomannan were pH 5.5 and a temperature of 65℃ with an IC50 value of 39.603 µg/mL due to the influence of pH and temperature on antioxidant activity, where low pH will have high antioxidants and high temperatures will cause a considerable reduction, resulting in high antioxidants.